Penggunaan Layanan Aplikasi Google Classroom Untuk Meningkatkan Hasil Belajar Fisika Mahamahasiswa Universitas Bina Insan - Eka Maryam Eka Maryam (Journal of Education and Culture (JEC), 2021)
The Covid-19 pandemic that hit countries around the world, including Indonesia, resulted in learning to be done online. One type of online learning application that can be used in online learning is google classroom. Google classroom is a learning application that functions to connect teachers and students in teaching and learning activities such as distributing materials, learning videos and assessing assignments online. This study aims to determine the use of the google classroom application in improving student learning outcomes in the physics course at the Faculty of Agriculture, Bina Insan University. The research method used is a pre-experimental method with a one group pretest-posttest design research design. As samples in this study were all students of the first semester of agriculture faculty of Bina Insan University. Data collection techniques using tests. The results of the study showed that learning outcomes using e-learning learning methods using the Google Classroom application on Physics subjects can improve student learning outcomes (N-gain) in moderate criteria.